Organizational And Informational Provision Of Fiscal Security Through Modernization Of The Customs System - V. V. Borsa; M. I. Miroshnichenko (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2025)
The article examines the organizational and informational support of fiscal security through the modernization of the customs system. The purpose of the study is to analyze the current state of fiscal security of the customs authorities of Ukraine and determine its role in strengthening the competitive positions of Ukraine in the context of digitalization and European integration. Research methodology: statistical analysis of the dynamics of modernization of the customs system since the independence of Ukraine. Research results: when carrying out a comparative characteristic of the main provisions of the Customs Codes of Ukraine as of 01.11.2025, it was found that the largest number of changes falls on 2022 – 2023; individual indicators of special customs statistics of declaration indicate that almost 100% of customs declarations are submitted and processed electronically, and this process has been stable in recent years. Practical significance of the study: recommendations for the implementation of European standards to increase the institutional capacity and investment attractiveness of the customs system of Ukraine in ensuring the fiscal security of the state.